Financial literacy, financial judgement, and retirement self-efficacy of older trustees of self-managed superannuation funds. (August 2015) - Earl, Joanne K; Gerrans, Paul; Asher, Anthony; Woodside, Julia
We investigate relationships between retirement self-efficacy, financial literacy and financial judgement across a sample of older trustees of self-managed superannuation funds (SMSFs). Aside from demographic factors, we explore self-rated dementia behaviours, general mental ability, mastery and risk tolerance. An increasing number of older people are controlling significant assets, particularly those who elect to become self-managed superannuation fund trustees. The ageing population, including self-managed superannuation fund trustees, is susceptible to cognitive decline with advancing age. We find that cognitive ability and self-rated behavioural dementia symptoms both relate to financial literacy. Variance in retirement self-efficacy was explained by age, cognitive ability, financial literacy, mastery and self-rated behavioural dementia symptoms. Those reporting dementia symptoms appear more vulnerable to making poor financial judgements. Findings have important implications for financial literacy interventions and the monitoring of on-going cognitive decline.